School without a head teacher: one-teacher primary schools in Bangladesh - Nath, Samir Ranjan (BRAC Research and Evaluation Division (RED), 2020)
Although there is no person called head teacher in BRAC's non-formal primary schools, however, the programme organisers (PO), each of whom look after 12-15 schools, playa pivotal role in the operation of BRAC schools. This paper assessed the role of POs in the management of BRAC schools. This is done in the light of the role that the head teachers in formal primary schools do. The POs do not teach in the classrooms but they visit schools twice a week, assess students' and teachers' performance through classroom observation and surprise tests of the students, guide the teachers to better teaching and in preparing monthly lesson plans, conduct monthly refreshers' training of the teachers and attending meetings of the parent-teacher associations. The POs also visit students at their homes. Compared with the role of a school head teacher it can be said that a PO plays a significant role in the management of BRAC schools.